Higher Maintenance Adalimumab Trough Levels are Associated With Achievement of Advanced Remission Targets in Patients With Inflammatory Bowel Disease. Issue 9 (October 2021) - Ritter, Einat; Hirsch, Ayal; Isakov, Naomi F.; Ron, Yulia; Cohen, Nathaniel A.; Maharshak, Nitsan
Abstract : Background: Biomarker normalization and endoscopic remission are superior to clinical remission in achieving improved long-term clinical outcomes in patients with inflammatory bowel diseases. Goal: To study whether higher maintenance adalimumab levels are associated with clinical remission, biomarker normalization, and endoscopic remission. Study: Data were collected retrospectively from the patients' medical records. We defined clinical remission as a Harvey Bradshaw Index ⩽5 or a partial Mayo score ⩽2 for Crohn's disease (CD) and ulcerative colitis (UC), respectively, biomarker normalization as a C-reactive protein <0.5 mg/dL and/or calprotectin <250 (mg/kg), endoscopic remission as a (simple endoscopic score-CD) ⩽3/4 for ileal/extensive CD, respectively, or an endoscopic Mayo score ⩽1 for UC, and deep remission as the combination of clinical and endoscopic remission with normal biomarkers. Results: Ninety-seven patients were included (82 CD and 15 UC). Patients who achieved clinical remission, biomarker normalization, or endoscopic remission had higher serum trough adalimumab levels compared with patients not in remission [mean (M)±standard error (SE)=8.98±0.78 vs. 5.92±0.96 μg/mL; P =0.016, 9.38±0.85 vs. 5.48±0.87 μg/mL; P =0.002; 9.13±0.88 vs. 6.02±0.77 μg/mL; P =0.019, respectively]. Receiver-operating curve analysis showed that an adalimumab level of ≥8.25 μg/mL was associated with deep remission (sensitivity 84%, specificity 70%, area under the curve 0.775; P <0.001). Conclusion: Clinical remission, biomarker normalization, and endoscopic remission are positively associated with adalimumab trough levels. Adalimumab level of ≥8.25 μg/mL is associated with deep remission. This study provides additional data to guide therapeutic drug monitoring with adalimumab.